A Comparative Analysis of the ADOS-G and ADOS-2 Algorithms: Preliminary Findings. - Dorlack, Taylor P.; Myers, Orrin B.; Kodituwakku, Piyadasa W. (Journal of Autism & Developmental Disorders, 2018)
The Autism Diagnostic Observation Schedule (ADOS) is a widely utilized observational assessment tool for diagnosis of autism spectrum disorders. The original ADOS was succeeded by the ADOS-G with noted improvements. More recently, the ADOS-2 was introduced to further increase its diagnostic accuracy. Studies examining the validity of the ADOS have produced mixed findings, and pooled relationship trends between the algorithm versions are yet to be analyzed. The current review seeks to compare the relative merits of the ADOS-G and ADOS-2 algorithms, Modules 1-3. Eight studies met inclusion criteria for the review, and six were selected for paired comparisons of the sensitivity and specificity of the ADOS. Results indicate several contradictory findings, underscoring the importance of further study.